Enhancing the CO Oxidation Performance of Copper by Alloying with Immiscible Tantalum - Song, Yi; Liu, Yu; Liu, Wenwei; Zhao, Zhiyi; Liu, Xiaoqiong; Xu, Ying; Li, Tao (ACS applied materials & interfaces, 2025)
Copper–tantalum (Cu–Ta) immiscible alloy nanoparticles (NPs) have been the subject of extensive research in the field of structural materials, due to their exceptional nanostructural stability and high-temperature creep properties. However, Cu is also a highly active oxidation catalyst due to its abundant valence changes. In this study, we have for the first time obtained homogeneous Cu x Ta1–x (x = 0.5, 0.7, 0.9, 1) nanoparticles by wet coreduction with an average particle size of approximately 30 nm. Testing verified all the Cu x Ta1–x /TiO2 (x = 0.5, 0.7, 0.9) showed higher CO oxidation activity than Cu/TiO2, with Cu0.7Ta0.3/TiO2 exhibiting the most promising performance. The temperature-programmed reduction with hydrogen demonstrated that Cu0.7Ta0.3/TiO2 exhibits enhanced redox properties. While kinetic studies indicated that the reaction of the Cu0.7Ta0.3/TiO2 catalyst followed the Langmuir–Hinshelwood mechanism, in situ diffuse reflectance infrared Fourier transform spectroscopy (in situ DRIFTS) verified the introduction of Ta induced the generation of bicarbonate as an intermediate product and increased the adsorption capacity of Cu+ on CO in the catalyst, which facilitated the reaction of surface adsorbed CO with oxygen and led to the enhanced CO oxidation activity.